2005
DOI: 10.1177/155335060501200308
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Objective Assessment of Knot Quality With a Portable Tensiometer Is Superior to Execution Time for Assessment of Laparoscopic Knot-Tying Performance

Abstract: Time to complete a knot is a poor metric for the objective assessment of intracorporeal knot-tying performance in the absence of a measure of knot quality. Real-time evaluation of the knot quality can accurately distinguish well-tied knots from poorly tied knots. This mode of assessment should be incorporated into training curriculum for surgical knot tying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…Ritter et al showed that the knot quality measured with a tensiometer was superior to execution time for the assessment of laparoscopic knot-tying performance [10]. The objectivity of the assessment could have been further increased if we had determined the quality of the knot as well, for example, by determination of the knot quality score.…”
Section: Discussionmentioning
confidence: 99%
“…Ritter et al showed that the knot quality measured with a tensiometer was superior to execution time for the assessment of laparoscopic knot-tying performance [10]. The objectivity of the assessment could have been further increased if we had determined the quality of the knot as well, for example, by determination of the knot quality score.…”
Section: Discussionmentioning
confidence: 99%
“…The first VR simulators in surgery (e.g., the MIST VR [20]) presented abstract tasks with geometric bodies in a synthetic environment, using single criterions such as time to complete a trial or counting of errors, for both validation and assessment. However, it is doubtful whether these common metrics are sufficient to assess surgical performance comprehensively [21][22][23][24][25]. Recent high-fidelity simulators present very realistic simulated surgical scenes, implementing more and more combinations of metrics and scoring systems which express common clinical skills, e.g., ''economy of movements'' [17] or ''precision'' [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, vaginal closure is obtained with the placement of a single intra-corporeal knot. The fact that we have not experienced any unsecured or unraveled knots is compelling, particularly given the high frequency of knot slippage reported in previous studies [10,11].…”
Section: Discussionmentioning
confidence: 87%
“…Many techniques have been devised to facilitate extracorporeal and intra-corporeal knot suturing in a costeffective and efficient manner [10][11][12][13]. In terms of extra-corporeal knot tying, the Roeder procedure employs a spiral sliding knot that expands with humidity, ensuring knot security and reliability [10].…”
Section: Discussionmentioning
confidence: 99%